The Effect of Guano Fertilizer Application and Poc Super Bionik Concentration on the Growth and Yield of Pagoda Mustard (Brassica Narinosa L.) - Mahya Indah Akmala; A. Miftakhurrohmat (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to determine the effect of the interaction between guano fertilizer and super bionic POC on the growth and yield of pagoda mustard plants grown on land in Ketapang Suko Village from December to February. This study was designed as a factorial design in a randomized block design (RBD). The first factor was the application of guano fertilizer, which consisted of three levels: 0, 5, and 10 g/plant. The second factor was the application of POC Super Bionik with three treatment concentrations, namely: 0, 2, and 4 ml/L, resulting in 9 treatment combinations repeated 3 times. The variables observed were plant height, number of leaves, leaf area, wet weight, dry weight, vitamin C test, and harvest index. The data were analyzed using analysis of variance followed by BNJ test. The results showed that there was no significant interaction between guano fertilizer application and POC Super Bionik concentration. Guano fertilizer application had a significant effect on plant height, number of leaves, wet weight, dry weight, and vitamin C test, while it had no significant effect on leaf area and harvest index. Guano fertilizer at a dose of 10 g/plant produced the highest wet weight. The application of POC Super Bionik on pagoda mustard plants had a significant effect on plant height, number of leaves, wet weight, and vitamin C test, while it had no significant effect on dry weight, leaf area, and harvest index. POC Super Bionik at a concentration of 2 ml/L produced the highest wet weight compared to other treatments. In conclusion, the application of Guano fertilizer had a significant effect on plant height, number of leaves, wet weight, dry weight, and vitamin C test, while POC Super Bionik had a significant effect on plant height, number of leaves, wet weight, and vitamin C test.